Mefloquine in infants and young children. - Luxemburger, C; Price, R; Nosten, F; Ter Kuile, F; Chongsuphajaisiddhi, T; White, N (1996)
In an area where multi-drug resistance in Plasmodium falciparum is a particular problem, more than 500 children under 5 years of age weighing > 5 kg were treated with mefloquine, either alone or combined with an artemisinin derivative, and followed up for a minimum of 28 days. The principal adverse effect was vomiting and this was associated with reduced efficacy of treatment (even when treatment was repeated). Later adverse effects occurred less frequently than in adults. There was no serious toxicity and, in particular, there were no neuropsychiatric side-effects. The high dose of mefloquine (25 mg/kg) required in this area is well tolerated by young children. It should be given in a divided dose of 15 mg/kg initially, followed by 10 mg/kg > or = 12 hours later.